Characterization and pathogenicity of Fusarium species complex associated with Fusarium wilt of banana in Malaysia - Ujat, Anysia Hedy (2021)
The emergence of the Fusarium wilt of banana (Panama disease) caused by Fusarium oxysporum f. sp. cubense Tropical Race 4 (Fusarium odoratissimum) which caused loss to the global banana production is known to infect majority banana cultivar. A total of 38 isolates of Fusarium spp. related to banana Fusarium wilt obtained from the Biological Control Laboratory, Department of Plant Protection, Faculty of Agriculture, Universiti Putra Malaysia were cultured on different media for observation of culture characteristics. Based on the culture morphology, isolates are grouped into four different group and a representative isolate were chosen for each group, namely Prk 4-1, Ns 5-2, Phg 3 and Swk 4. Micromorphology shows no significant difference in the macro- and microconidia size. To further identify the isolates, molecular analysis was conducted by using the sequences of Histone H3 gene and TEF-1α gene. TR4 specific primers were used to confirm the presence of Fusarium odoratissimum (TR4). The phylogenetic tree using Histone H3 sequences showed all isolates grouped into Fusarium oxysporum species complex while phylogenetic tree using TEF-1α sequences revealed that the samples were composed of 27 isolates of Fusarium odoratissimum (TR4), two isolate Fusarium grosmichelii (R1), six unknown Fusarium oxysporum species complexes isolates and three Fusarium fujikuroi isolates. By using TR4 specific primers, all 27 samples were confirmed to be Fusarium odoratissimum (TR4). To study the susceptibility of local banana cultivar, pathogenicity test was conducted on 3 months old banana plantlets consisting of five different local banana cultivars of three different genome types: Musa acuminata AAA (Pisang Berangan and Pisang Serendah), Musa paradisiaca AAB (Pisang Nangka and Pisang Raja) and Musa balbisiana BBB (Pisang Nipah). Observation was recorded for 30 days, and foliar symptoms showed different severity of disease progression. However, internal symptoms showed that all of the inoculated plantlets were severely infected. Cooking banana (AAB and BBB) of local cultivar were also found to be susceptible to Fusarium odoratissimum (TR4). This study shows that there are not only Fusarium odoratissimum (TR4) presence in Malaysia but also Fusarium grosmichelii (R1) and a possibility of an unknown strain of Fusarium oxysporum. Pathogenicity test reveals that local banana cultivar in Malaysia are susceptible to Fusarium wilt disease regardless of the genotype of the banana plants. These findings will aid in the substantive documentation of Fusarium spp. in the local banana plantation scenario.